TRANSFORMATIVE PEDAGOGY IN PRESENT AND SUBSEQUENT SOCIAL CHANGE - Afriadi, Bambang; Kaswati, Ryka; Tjalla, Awaluddin; Sutisna, Anan (International Journal of Business, Law, and Education, 2022)
Education is one of the critical areas in the development of the country. Education is an essential instrument for bringing about a social revolution, and the attachment of education to social change will successfully refer to ideas. Education is changing the way traditions look and approach social issues. Compiling this article using the systematic review method is a comprehensive review of labor-intensive activities. It may require evaluating hundreds of articles before identifying studies that meet the specified eligibility criteria. The result of the systematic review method that transformative education empowers teachers and learners, namely encouraging teachers and learners to become reflective and critical thinkers who can make meaningful contributions as members of local and global communities